Plasma alkylresorcinol metabolite, a biomarker of whole-grain wheat and rye intake, and risk of ischemic stroke: a case-control study. Issue 2 (7th February 2019) - Sun, Taoping; Zhang, Yanwei; Huang, Hao; Wang, Xiaoqian; Zhou, Li; Li, Shuzhen; Huang, Suli; Xie, Changhui; Wen, Ying; Zhu, Yalun; Hu, Xiaoli; Chen, Liangkai; et al.
ABSTRACT: Background: Epidemiologic studies on whole grains and risk of stroke have reported inconsistent results, with some suggesting a protective effect but others showing a null association. Objectives: The aim of this study was to examine whether plasma 3-(3, 5-dihydroxyphenyl)-1-propanoic acid (DHPPA), a biomarker of whole-grain wheat and rye intake, is associated with risk of ischemic stroke. Methods: A hospital-based case-control study was conducted between March 2011 and May 2016. Cases ( n = 990) with first ischemic stroke were matched to controls ( n = 990) by sex and age. Concentrations of plasma DHPPA were determined by high-performance liquid chromatography–tandem mass spectrometry. We calculated ORs for the association of plasma DHPPA concentrations with ischemic stroke risk through the use of logistic regression. Results: Plasma DHPPA was inversely associated with ischemic stroke risk. After adjustment for potential confounding factors, the ORs for ischemic stroke across increasing quartiles of plasma DHPPA concentrations were 1 (referent), 0.76 (95% CI: 0.58, 0.99), 0.71 (95% CI: 0.54, 0.92), and 0.59 (95% CI: 0.45, 0.77), respectively ( P -trend = 0.001). The inverse association was also observed in all subgroups of participants according to sex, age, body mass index, smoking status, alcohol consumption, history of hypertension, and history of diabetes. Conclusions: Our study showed that higher plasma DHPPA concentrations were associated with lower risk of ischemic stroke. This finding provides further evidence to support the health benefits of whole-grain consumption.